THE PRINCIPLE OF HUMANISM AND ITS ROLE IN MODERN SOCIETY - Ismoilov Odilbek Temirpulatovich (Bright Mind Publishing, 2025)
The principle of humanism is a fundamental concept that emphasizes the value, dignity, and rights of every individual. This article explores the theoretical foundations of humanism, its historical development, core values, and its practical application in modern society, analyzes the philosophical and ethical aspects of humanism, highlighting its evolution from ancient civilizations to contemporary global ethics. And examines the implementation of humanistic principles in governance, education, social policy, and technology, illustrating how these values contribute to inclusive, just, and sustainable development. The article also identifies challenges to implementing humanism, such as social inequality, political instability, and ethical dilemmas in technology, and discusses prospects for strengthening humanistic values in the XXI century.
Keywords: Humanism, human rights, dignity, equality, education, governance, social policy, ethics, sustainable development.